-4(3x-7)=-12x-28

Simple and best practice solution for -4(3x-7)=-12x-28 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4(3x-7)=-12x-28 equation:


Simplifying
-4(3x + -7) = -12x + -28

Reorder the terms:
-4(-7 + 3x) = -12x + -28
(-7 * -4 + 3x * -4) = -12x + -28
(28 + -12x) = -12x + -28

Reorder the terms:
28 + -12x = -28 + -12x

Add '12x' to each side of the equation.
28 + -12x + 12x = -28 + -12x + 12x

Combine like terms: -12x + 12x = 0
28 + 0 = -28 + -12x + 12x
28 = -28 + -12x + 12x

Combine like terms: -12x + 12x = 0
28 = -28 + 0
28 = -28

Solving
28 = -28

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 5x+15=3(x+5) | | 112x=245x+95 | | 5.5=7.9-0.6x | | x-41=70 | | 7=-x+264 | | y+51=89 | | -37-8= | | h(t)=-16t^2+20t+17 | | x(x+3)-5=3x+20 | | 3x+7-5(x+1)=2x+5 | | 5y+3y-5=6(4y+3) | | -4s+9=-24 | | 2r+4=-16 | | (6+9)x=15x | | 10z^2+17z-20= | | 8y-12y+9=24-y | | 120-x=3x | | 3(r+1)-1[2(3-2r)-3(3-r)]=2(r+5)-4 | | 120+.40x=50+.60x | | 1/2x-5x | | 120x+.40=50x+.60 | | 5(2m+3)-1(1-2m)=2[3(3+2m)-1(3-m)] | | 2x(50-15)=2y | | 16vw^2x^3-28v^4w^4= | | 4(x+9)-6(9x-5)=14 | | y-9=25 | | 9(3x+6)=-x(x-2) | | 2[5(w+3)-1(w+1)]=3(1+w) | | (4/9x)/(2/3x) | | 1x+3+2x=-8 | | 4k^2-7k=2 | | 2(n+7)=8-n |

Equations solver categories